English Communication for a Staff Car Dealer Company in Pathumtani Province, Thailand: Thesis - Thongsookularn, Sookchok (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2020)
The purpose of this research aimed at. Firstly, to study the ability of English communication for a staff car dealer company in Pathumthani province, Secondly, to analyze the frequency of using English communication for a staff car dealer company in Pathumthani province and 3) and to propose the ways of English communication solving for a staff car dealer company in Pathumthani province. This study was a mixed-method between qualitative and quantitative research in nature. A questionnaire was used for collecting quantitative data form 60 staffs and an in-depth interview was used for collecting qualitative data from 7 key informants. An analyzing quantitative data statistic including Frequency, Percentage, Mean and Standard Deviation (SD) was used and a content analysis was used for analysis. Results of the study were as follows: From study ability of English communication for a staff car dealer company in Pathumthani province, it was found that the first part of study ability of English communication was (= 2.72). So, it can be interpreted that the students had a medium level, and second part was the frequency of using English communication was ( = 4.26). Which is interpreted as being at high level. The analysis frequency of using of English communication for a staff car dealer company in Pathumthani province. It revealed that frequency of using of English communication was (= 3.82). Which was interpreted as being at high level. Regarding propose the ways to develop English communication for staff car dealer company in Pathumthani province, It found that they were required to study the biggest challenge to develop English communication skill by the of practice self-learning, did not be afraid of, did not be shy and fearful, English business was very important for many things in daily life, strategy of good speaker was seeking for the way to express to speak English in the public speaking that they did not feel nervous or fear when they speak English, learning English effectively was not be afraid to make mistakes when speaking English, be confident, made sure that you get lots of practicing and used it real situation such as seminars, meetings or conference, the process of communication was step of effective communication from customer service representatives is imperative to solving problems quickly, study International Phonetic Alphabet in order to know how to pronounced and to spoke English, ideas to speak English with customers are to talk with them in English while making sales and meeting their needs, overcoming shyness and fear were necessaries, international trade agreements are concluded in English, improving English by YouTube, TV, podcast, BBC, VOA, English conversation, chat on Facebook and group discussion were fruitful for the English improving. Moreover, the company should provide a budget to improve the staff’s English communication. For instance, the budget for training English or employee seminar both internal and external countries.